A critical study on safety issues – special reference to bus conductors in selected routes of Jaffna, Sri Lanka - Thanushan, R. (South Eastern University of Sri Lanka, 2016)
Generally, people happen to face too many problems during travels and transportation but they find it very difficult to immediately find a solution to such problems. All the passengers around the world, specially, in under developed countries face too many problems. Now I wish to point out that bus conductors seem to cause safety issues in Jaffna with regard to the route services. The main objective of this study is, identifying the safety issues created by bus conductors. This is found out through this research. Twenty six participants have been included for the in-depth interview.(eight private mini-bus conductors, six Sri Lankan Transport Bus(SLTB)conductors, twelve passengers). The collected primary data have been analyzed by the “Thematic analysis”, “Descriptive statistical analysis” and “Human narrative analysis”. As a result, it is also found that 100% samples of private mini-bus conductors have no their Ordinary Level (O/L) qualification whereas 60% samples of SLTB conductors have passes in three or four subjects in the Advanced Level (A/L) examination. It is to be noted that 100% samples of private mini-bus conductors did not take their training for the job even for a day. Some issues such as failure in returning balance immediately, overcrowding, and sudden delay in service for no reason. In addition, both bus conductors create unnecessary problems such as improper ticketing system, unavailability of emergency facilities and noise distraction. These issues have been clearly identified. Therefore it is suggested that the above issues could be avoided by taking immediate actions through safety methods with the help of the Authorities concerned.
Keywords: Safety Issues; Passengers; Mini-bus Conductors; Route Services